(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Education is an investment to development and poor study methods should not compromise the mandate of higher education institutions to generate, preserve and disseminate knowledge and produce high quality graduates. Universities admit studentswith varying backgrounds in terms of learning/study styles, levels of preparedness andconcepts of university education. Some were "drilled", spoon fed, taught for exams, orhave wrong purposes/values of university learning. These negatively impact on theirstudy skills and achievement. In complementing the role played by academic staff,students need to be conscious of their personality and study ethics as they influence studying. It is futile to teach well while students lack the fundamentals to conceptualize and internalize the new knowledge. This paper proposes a paradigm shift in studymethods and suggests strategies for both the lecturers and the students in universities towards improved learning and performance. The paper is based on the "distributedlearning approach" to adequately cater for individual differences that exist among thestudents. The model is significant for university students, most of whom begin seriousstudying on realization that examinations are around the corner. This causes stress,confusion and tendency to cheat in examinations. Distributed learning model will address the study space needs and theefficiency and effectiveness of study methods